TINJAUAN YURIDIS PEMBATALAN PUTUSAN ARBITRASE OLEH PENGADILAN NEGERI DITINJAU DARI UU NO 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA (Studi Kasus Perkara Nomor 861/Pdt.Sus-Arbt/2023/PN.Jkt.Brt) - Lia Amalia; Mela Mustika; Muhamad Abas; Saprudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Arbitration as an alternative to resolving business disputes offers a fast, confidential, and final process, but this finality is limited by the provisions of Law Number 30 of 1999 which allows for cancellation under certain conditions. This normative legal research analyzes the legal basis for the cancellation of an arbitration award through a case study of the West Jakarta District Court Decision Number 861/Pdt.Sus-Arbt/2023/PN.Jkt.Brt. The results of the study show that cancellation is only permitted based on three limiting reasons in Article 70 of the Arbitration Law. In the case of PT Talkindo Selaksa Anugrah, the judge annulled the BANI decision based on the discovery of important hidden documents and the existence of trickery. The judge's considerations reflect the balance between maintaining the principle of finality of arbitration and upholding substantive justice, although the standard of proof applied is more flexible than international standards. The annulment of an arbitration award must still be seen as an extraordinary corrective mechanism that is applied strictly, without sacrificing the integrity of the arbitration process, because finality should not protect dishonest practices in dispute resolution.